Tubal schistosomiasis in Brazilian women: a case report - Orlandini, L F; Munhoz, A S B; Nogaroto, M; Galão, E A; Bagarelli, L B; Oliani, A H (Prague medical report, 2009)
Several authors have reported schistosomiasis caused by Schistosoma haematobium in the female genital tract of patients in endemic areas. This work describes tubal schistosomiasis by Schistosoma mansoni in a Brazilian woman submitted to hysterectomy for uterine myomatosis and metrorrhagia. Macroscopy evidenced hydrosalpinx of the left tube and multiple Schistosoma mansoni eggs were identified by anatomopathological examination. This article illustrates a rare form of schistosomiasis as the cause of tubal damage.
Keywords: Adult; nemoci vejcovodů; lidé; dospělí; schistosomiasis mansoni; ženské pohlaví; Female; Schistosomiasis mansoni; Humans; Fallopian Tube Diseases